'The association that dissociates' – narratives of local political resistance in Kosovo and the delayed implementation of the Brussels Agreement. Issue 2 (3rd April 2018) - Troncotă, Miruna
ABSTRACT: The existing literature on the EU's transformative role in the Balkans looks at EU conditionality as a unidirectional system of rewards that is expected to motivate local elites to comply with EU rules. This article raises a different question: how do local actors bypass the implementation phase of EU conditionality and what kind of political resistance narratives do they use for this purpose? The analysis attempts to tackle these inter-related questions by focusing on the delayed implementation of the Brussels Agreement between Belgrade and Pristina as a case study, using the interpretive method of narrative analysis. The article aims to link fieldwork empirics with theoretical discussions in the field of EU compliance literature by stressing the importance of local actors' resistance to EU incentives. Three levels of analysis will be conducted in order to address the research question: (1) mapping different types of actors at the local level and stressing their heterogeneity; (2) understanding how local resistance to EU pressure evolved in the period 2013–2016; and (3) showing how their policy narratives influenced the implementation phase and the maintenance of the status quo. In conclusion, the analysis shows that the EU's mediation strategy of 'constructive ambiguity' favours local actors' political resistance, particularly in the implementation phase. The main findings show that 'dividers' outnumber 'connectors' in local actors' narratives, thus strengthening political resistance to EU pressure.